Exploring Network Governance as an Alternative Model for Green Open Space (RTH) Management in Indonesia: A Systematic Literature Review - Rahmanto, Muhammad Adhika (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This paper explores the concept of network governance and its potential application in managing Ruang Terbuka Hijau (RTH), or green open spaces, in urban Indonesia. Despite the Indonesian government's regulation mandating 30% of urban areas to be allocated for RTH, only a fraction of cities have met this requirement, and governance inefficiencies remain a significant barrier. This study uses a Systematic Literature Review (SLR) methodology, adhering to the PRISMA 2020 approach, to assess how network governance can be applied to overcome the challenges faced in managing green spaces. The review identifies key studies, actors, and themes within network governance, highlighting its potential to improve collaboration, resource sharing, and stakeholder engagement in RTH management. The findings suggest that network governance offers a promising framework for fostering collaboration among local governments, community groups, and private sectors, addressing issues like limited resources, spatial planning deficiencies, and political will. This paper concludes by proposing a roadmap for future research and policy applications to enhance urban resilience through effective green space governance.